Below‐cloud scavenging of fine and coarse aerosol particles by rain: The role of raindrop size. (21st November 2018) - Blanco‐Alegre, Carlos; Castro, Amaya; Calvo, Ana I.; Oduber, Fernanda; Alonso‐Blanco, Elisabeth; Fernández‐González, Delia; Valencia‐Barrera, Rosa M.; Vega‐Maray, Ana M.; Fraile, Roberto
Abstract : Below‐cloud aerosol scavenging is an important process to remove particles from the atmosphere. In this study, both precipitation (measured with a laser disdrometer registering drops between 0.125 and 8 mm) and atmospheric aerosol particles (measured with a Passive Cavity Aerosol Spectrometer Probe registering aerosol sizes between 0.1 and 24 µm) have been sampled on a 1 min basis. Based on 6 months of outdoor measurements in León (northwest Iberian Peninsula), the scavenging coefficients were calculated for the aerosol particles measured, with a mean value of 2.6 × 10 −5  ± 6.0 × 10 −5  s −1 for the fine mode and 5.8 × 10 −5  ± 9.6 × 10 −5  s −1 for the coarse mode in 54 rain events. Likewise, the particle concentration decreased during rain by 10%, and by 18% between the time before and after the rain. In the Greenfield Gap (sizes between 0.3 and 1 µm) the scavenging is less effective, mainly between 0.6 and 1 µm, than with smaller particles. The number of drops between 0.75 and 3 mm shows statistically significant ( p  < 0.05) negative correlations with the number of particles between 0.16 and 1.76 µm, thus illustrating the potential of those raindrops to favour the scavenging of particles of that size. In addition, there were statistically significant negative correlations between the total volume removed by falling drops (mm 3 /m 3 ) and the variation of the number of particles in channels with diameters between 0.12 and 0.19 µm. Abstract : This study focuses on the role of raindrop sizes in the scavenging of aerosol particles based on 6 months of outdoor measurements in León, Spain. Raindrops with diameters between 0.75 and 3 mm produce a higher scavenging on particles between 0.16 and 1.76 µm. The scavenging coefficients had a mean value of 2.6 × 10 –5  s –1 for the fine mode and 5.8 × 10 –5  s –1 for the coarse mode.